Repeated application of transcranial ultrasound maintains spatial and recognition memory in 5xFAD mice with reduction of amyloid-β burden - Seung-Schik Yoo; Anvita Reddy; William Carroll; Kanyapat Ploypradith (PLoS ONE, 2025)
Pharmacological removal of amyloid beta protofibrils has emerged as a promising therapeutic strategy to delay the onset of Alzheimer’s disease (AD) symptoms. As a non-pharmacological and noninvasive alternative, transcranial application of low-intensity ultrasound through intact skull can induce convective acoustic streaming, which has been shown to enhance cerebrospinal fluid solute transport and facilitate the clearance of interstitial solutes. This has led to the development of device-based approaches aimed at removing the precursors of amyloid beta (Aβ) plaques and mitigating cognitive decline in AD. We applied non-thermal, non-cavitational ultrasound (400 kHz frequency) in a pulsed mode (75 ms pulse duration, 2 Hz repetition rate) to the hippocampal region of male 5xFAD mice for 30 minutes weekly, starting at 10 weeks of age and continuing for 15 weeks (until 6 months of age). Spatial and recognition memory performance was assessed monthly using the Y-maze spontaneous alternation (SA) and novel object recognition (NOR) tests. A control group of age-matched mice underwent the same procedures with receiving zero acoustic output. Mice subjected to transcranial ultrasound (tUS) treatment maintained both SA and NOR performance throughout the entire experimental period, whereas mice that received sham tUS exhibited a progressive decline in memory beginning at 3–4 months of age. Congo Red staining of the brain sections revealed a significant (> 40%) reduction in Aβ plaques in the sonicated group. Histological analysis confirmed that repeated ultrasound exposure did not cause any detectable tissue damage. These findings suggest that low intensity tUS may serve as a novel, noninvasive therapeutic strategy to delay the onset of AD symptoms through the reduction of Aβ burden.